2016
DOI: 10.1111/tbj.12626
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of pN0 Triple-Negative Breast Cancer with or without Lymph Node Irradiation: A Single Institution Experience

Abstract: The optimal management of patients with pathologically node-negative triple-negative breast cancer (pN0 TNBC) remains unclear. We hypothesized that lymph node irradiation (LNI; internal mammary chain/periclavicular irradiation) had an impact on outcomes of pN0 TNBC. A cohort of 126 consecutive patients with pN0 TNBC treated between 2007 and 2010 at a single institute were included. All radiotherapy (breast/chest wall, ±LNI) was delivered adjuvantly, following completion of surgery ± chemotherapy. Tumors were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Previous experiences used different definitions for both OS and EFS. While some authors defined it as the time from diagnosis until the event (death or recurrence) [12,13,26,40], others start the follow-up from the treatment date (medical or surgery) [10,29,41]. This latter approach prevents incurring an immortal time bias in the survival analysis by avoiding the observation time of patients without therapy.…”
Section: Plos Onementioning
confidence: 99%
“…Previous experiences used different definitions for both OS and EFS. While some authors defined it as the time from diagnosis until the event (death or recurrence) [12,13,26,40], others start the follow-up from the treatment date (medical or surgery) [10,29,41]. This latter approach prevents incurring an immortal time bias in the survival analysis by avoiding the observation time of patients without therapy.…”
Section: Plos Onementioning
confidence: 99%
“…A recent study reported that women with T1‐2N0 TNBC treated with modified radical mastectomy without radiotherapy had a significantly increased risk of locoregional recurrence and poorer survival . On the other hand, another study revealed that omission of radiotherapy in patients with pN0 TNBC did not seem to result in poorer outcome . Those previous reports investigating the survival outcomes of TNBC patients according to local radiotherapy status have produced conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…Radiotherapy (RT) is an important component in the treatment of breast cancer, especially as an adjuvant approach in breast conserving therapy. Postoperative irradiation is also getting continuously important in the management of the TNBC subtype, although the benefit is still debatable, concerning overall survival ( 10 , 11 ). Recent studies revealed no differences in dose fractionation adding an evidence to support the use of moderate hypofractionated whole-breast irradiation in TNBC patients ( 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy for breast cancer can reduce the risk of a local relapse and decrease the risk of cancer-associated mortality in the patient and is therefore a crucial part of therapeutic options for the patient ( 7 9 ). While the benefit of radiotherapy concerning overall survival for patients with TNBC is still debatable ( 10 , 11 ), adjuvant radiotherapy is an indispensable part of breast conserving therapy assuring locoregional control. Thus, estimating the role of radiotherapy and the modalities of postoperative irradiation in the TNBC prognosis is continuously important.…”
Section: Introductionmentioning
confidence: 99%